(untitled) (GEON Journal (Management, Organizations and Business), 2018)
Colombia is a country with an economy based on SMEs, there are processes that need to be guided by IFRS standards, as is the case of the inventory sections (section 13), in accordance with which the objective was to propose guidelines for control and direction necessary for the management of inventories for SMEs. Method was the qualitative one that allowed recognizing the possible causes that prevent SMEs from achieving quality standards in inventories. The results revealed the lack of administration and control for the management of inventories both in the warehouse and in the store of veterinary products, concluding that the non-adoption of international standards did not allow them to properly exercise good accounting policies. under IFRS for SMEs and for this it was necessary to suggest control guidelines in their inventory management policies.